2009
DOI: 10.7589/0090-3558-45.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Tuberculosis in Cattle and Badgers in Localized Culling Areas

Abstract: ABSTRACT:Bovine tuberculosis (TB) is a zoonotic disease that can have serious consequences for cattle farming and, potentially, for public health. In Britain, failure to control bovine TB has been linked to persistent infection of European badger (Meles meles) populations. However, culling of badgers in the vicinity of recent TB outbreaks in cattle has failed to reduce the overall incidence of cattle TB. Using data from a large-scale study conducted in 1998-2005, we show that badgers collected on such localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 22 publications
4
71
0
Order By: Relevance
“…The utility of the approach has been demonstrated in New Zealand, where localized possum population control has been shown to cause subsequent reductions in the Tb reactor rate among adjacent cattle stocks (Caley et al 1999). However, in the UK and Ireland, the impact of experimental badger culling on concurrent disease in domestic stock is more complex, with culling both increasing and decreasing cattle Tb reactor rates, depending on the circumstances (Griffin et al 2005;Donnelly et al 2006;Carter et al 2007;McDonald et al 2008;Woodroffe et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The utility of the approach has been demonstrated in New Zealand, where localized possum population control has been shown to cause subsequent reductions in the Tb reactor rate among adjacent cattle stocks (Caley et al 1999). However, in the UK and Ireland, the impact of experimental badger culling on concurrent disease in domestic stock is more complex, with culling both increasing and decreasing cattle Tb reactor rates, depending on the circumstances (Griffin et al 2005;Donnelly et al 2006;Carter et al 2007;McDonald et al 2008;Woodroffe et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Such culling reduces badger density (17), but also promotes dispersal into the culled area (18) as well as expanding badger ranging in and around the areas where culls occurred (19). In Britain these behavioral changes-termed social perturbation-have been linked to increases in the proportion of badgers infected with M. bovis (13,20), and reductions in the spatial clustering of infection (21). In cattle, the incidence of confirmed TB was reduced inside large culling areas where badger numbers were substantially suppressed by annual "proactive" culling.…”
mentioning
confidence: 99%
“…By way of example, Woodroffe et al (2009) observe that field studies have so far found little to support the commonly assumed positive correlation between badger group size and bTB infection. Their own work on evidence from areas in the RBCT proactive culls suggests a lower than expected prevalence in large groups, although the size of those groups nevertheless meant higher absolute numbers of infected badgers, therefore maintaining the risk of spread to cattle.…”
Section: #5 Molecular Geographies and Statistical Modellingmentioning
confidence: 99%
“…More Defra-sponsored work is now proceeding on the home ranges of these bTB genotypes and it seems that each local variety has found expression in the bodies of both cattle and badgers (Olea-Popelka et al, 2005;Woodroffe et al, 2009). As a result, the interspecies pooling of infection is now more certain than ever, although Goodchild et al (2012) found that over short distances genotype dissimilarity is greater in cattle than in badgers and they conclude (page 8), as a result, that this is "evidence that cattle were exposed to other sources of infection", presumably other cattle.…”
Section: #5 Molecular Geographies and Statistical Modellingmentioning
confidence: 99%
See 1 more Smart Citation